2021
DOI: 10.3390/app11041899
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Acoustic Cameras Provide Direct and Efficient Assessments of Large Demersal Fish Populations in Extremely Turbid Waters

Abstract: Monitoring fish species populations in very turbid environments is challenging. Acoustic cameras allow work in very poor visibility but are often deployed as a fixed observation point, limiting the scope of the survey. A BlueView P900-130 acoustic camera was deployed in rocky marine habitats off the coast of French Guiana in order to assess the total abundance, size structure and spatial distribution of a demersal fish population. The relevancy of using an acoustic camera to achieve these three objectives was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…High counting accuracy is often achieved due to the high‐quality data obtained and the single swimming direction of migrating fishes. In addition, MFLS is also widely used in surveys of habitats, such as artificial reefs (Guo et al, 2018; Plumlee et al, 2020), estuary (Becker et al, 2016; Becker et al, 2017; Lankowicz et al, 2020), river (Hayes et al, 2015; Kerschbaumer et al, 2020; Mora et al, 2015), lake (Jing, Han, Wang, et al, 2018a), estuarine shoreline (Smith et al, 2021), offshore habitat (Artero et al, 2021; Tassetti et al, 2020; Van Hal et al, 2017), reservoir (Huang & Gong, 2020; Mo et al, 2015; Shen et al, 2018), etc., to study the fish stock and interaction of fishes with the habitats. The fish density is typically calculated to estimate abundance and studied for the habitat population distribution (Plumlee et al, 2020; Zhou et al, 2014).…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
See 3 more Smart Citations
“…High counting accuracy is often achieved due to the high‐quality data obtained and the single swimming direction of migrating fishes. In addition, MFLS is also widely used in surveys of habitats, such as artificial reefs (Guo et al, 2018; Plumlee et al, 2020), estuary (Becker et al, 2016; Becker et al, 2017; Lankowicz et al, 2020), river (Hayes et al, 2015; Kerschbaumer et al, 2020; Mora et al, 2015), lake (Jing, Han, Wang, et al, 2018a), estuarine shoreline (Smith et al, 2021), offshore habitat (Artero et al, 2021; Tassetti et al, 2020; Van Hal et al, 2017), reservoir (Huang & Gong, 2020; Mo et al, 2015; Shen et al, 2018), etc., to study the fish stock and interaction of fishes with the habitats. The fish density is typically calculated to estimate abundance and studied for the habitat population distribution (Plumlee et al, 2020; Zhou et al, 2014).…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
“…The ability of imaging sonar to monitor fish in turbid water has been highlighted by various researchers (Artero et al, 2021; Becker, Whitfield, et al, 2011b; Faulkner & Maxwell, 2020). Artero et al (2021) utilized BlueView sonar (900 kHz) to successfully assess fish abundance, length and spatial distribution in one of the world’s most turbid region French Guiana. Becker, Whitfield, et al (2011b) found the data quality was not appreciably different when the turbidity ranged from 5 to 28 nephelometric turbidity units (NTU).…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers take photos in a controlled laboratory environment using digital cameras or cell phones, then construct databases [26]. The quality of the obtained pictures determines the effectiveness of a fish classification system; however, water turbidity has been a key issue impacting the quality of the acquired images [27]. When the turbidity of the water affects the vision of the fish, several researchers have proven experimentally that frontal lighting with backlight images can produce rather acceptable results [28].…”
Section: Related Workmentioning
confidence: 99%